Church planting in the South African urban context – with special reference to the role of the Reformed Church Tshiawelo - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.